PERBEDAAN HASIL KADAR HEMOGLOBIN MENGGUNAKAN HEMATOLOGY ANALYZER DAN POCT - Zalfa, Anisatuz; Nugraha, Gilang; Wulan, Wieke Sri; Prayekti, Endah (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2024)
Hemoglobin is a protein molecule in red blood cells that carries O2 throughout the body. Hemoglobin contains iron which makes blood red. The hemoglobin level is a measure of the respiratory pigment present in the erythrocytes, which is used to determine anemia. This study was to see if there were differences in the results of hemoglobin levels using a hematology analyzer and POCT. This study used a hematology analyzer and POCT to determine the accuracy of the results obtained on the examination of hemoglobin levels. The aim of this study was to determine differences in the results of hemoglobin levels using a hematology analyzer and POCT. This type of research is analytic observational with a cross sectional approach. This study used venous blood samples using the hematology analyzer method and capillary blood samples using the POCT method as many as 54 samples. Collecting data using purposive sampling technique. The research was conducted in May 2023. The analytical test used the Independent T Test. Based on the research results, the p-value = 0.212 so that H0 is accepted, which means that there is no difference in the results of hemoglobin levels using a hematology analyzer and POCT. Based on the independent t test, the results obtained were a p-value of 0.212, which means that there was no difference in the results of hemoglobin levels using a hematology analyzer and POCT.